Ethnobotany, phytochennistry and pharmacology of medicinal plants belonging to the genus Baccharis (Astera ceas) used at Ayacucho city - Aguilar, Enrique (2007)
Spedes from Baccharis genus were studied fo the viewpoint ethnobotanical, chemical and pharmacological which are used as medicinal plants at de Ayacucho depaIllllent. Three species from Baccharis genus were collected from the Quinua district and the Muyurina VaHey (Huamanga province, Ayacucho), during april to june months of 2006. The ethnobotanical study was realized using the Caceres's methodologíe(I996) and the phytochemical study in according to Miranda and Cuellar (2000), prostaglandine El-induced rat paw oedema has been used as an anti-inflammatory model, the antioxidant activity was studied using the DPPH scavenger and the antimicrobial activity with the excavated plate model. The species were identified as B. salicifolia used as analgesic, anti-inflammatory and anti-rheumatic; B. genistelloides as anti-inflammatory and hepatic problems and of the B. glutinosa wasn't reported any know use. It were-isolated flavonoids oí type flavone and flavanone oE the leaves from the Bnccharis. B. saliczfolia has demonstrated have the best anti-intlammatory activity (p<O.OS) and antioxidant (p<O.05); while B. glutinosa has presented antimicrobialactivity againts Salmonella sp. and Shigella sonnei. Three species of Baccharis genus were identified as B. genistelloides,B. glutinosa y B. salicifolia; and the ethnobotanical study was performed reporting the traditional uses. The tlavonoids present are the flavone and flavonone type. B: Salicifolia was the best anti-inflammatory and antioxidant; B. glutinosa was the best antimicrobial.